The Effect of Green Synthesized CuO Nanoparticles on Callogenesis and Regeneration of Oryza sativa L. - Anwaar, Sadaf; Maqbool, Qaisar; Jabeen, Nyla; Nazar, Mudassar; Abbas, Fazal; Nawaz, Bushra; Hussain, Talib; Hussain, Syed Z. (Frontiers in Plant Science, 2016)
In this study, we have investigated the effect of copper oxide nanoparticles (CuO-NPs) on callogenesis and regeneration of Oryza sativa L (Super Basmati, Basmati 2000, Basmati 370 and Basmati 385). In this regard, CuO-NPs have been bio-synthesized via Azadirachta indica leaf extract. Scanning electron microscope (SEM) analysis depicts average particle size of 40±5 nm with highly homogenous and spherical morphology. X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) have been employed to confirm the phase purity of the synthesized NPs. It is found that CuO-NPs exhibit very promising results against callus induction. It is attributed to the fact that green synthesized CuO-NPs at optimum dosage possess very supportive effects on plant growth parameters. In contrast to callogenesis, differential regeneration pattern has been observed against all of the examined O. sativa L. indigenous verities. Overall observation concludes that CuO, being one of the essential plant nutrients, has greatly tailored the nutritive properties at nano-scale.